Targeting Neurons of Rat Nucleus Tractus Solitarii with the Gene Transfer Vector Adeno-Associated Virus Type 2 to Up-Regulate Neuronal Nitric Oxide Synthase - Lin, Li-Hsien (2011)
Adeno-associated virus (AAV) has distinct advantages over other viral vectors in delivering genes of interest to the brain. AAV mainly transfects neurons, produces no toxicity or inflammatory responses, and yields long-term transgene expression. In this study, we first tested the hypothesis that AAV serotype 2 (AAV2) selectively transfects neurons but not glial cells in the nucleus tractus solitarii (NTS) by examining expression of the reporter gene, enhanced green fluorescent protein (eGFP), in the rat NTS after unilateral microinjection of AAV2eGFP into NTS. Expression of eGFP was observed in 1–2 cells in the NTS 1 day after injection. The number of transduced cells and the intensity of eGFP fluorescence increased from day 1 to day 28 and decreased on day 60. The majority (92.9 ± 7.0%) of eGFP expressing NTS cells contained immunoreactivity for the neuronal marker, protein gene product 9.5, but not that for the glial marker, glial fibrillary acidic protein. We observed eGFP expressing neurons and fibers in the nodose ganglia (NG) both ipsilateral and contralateral to the injection. In addition, eGFP expressing fibers were present in both ipsilateral and contralateral nucleus ambiguus (NA), caudal ventrolateral medulla (CVLM) and rostral ventrolateral medulla (RVLM). Having established that AAV2 was able to transduce a gene into NTS neurons, we constructed AAV2 vectors that contained cDNA for neuronal nitric oxide synthase (nNOS) and examined nNOS expression in the rat NTS after injection of this vector into the area. Results from RT-PCR, Western analysis, and immunofluorescent histochemistry indicated that nNOS expression was elevated in rat NTS that had been injected with AAV2nNOS vectors. Therefore, we conclude that AAV2 is an effective viral vector in chronically transducing NTS neurons and that AAV2nNOS can be used as a specific gene transfer tool to study the role of nNOS in CNS neurons.